Perlindungan Homeworker Yang Berkerja Secara Putting Out System - Solechan Solechan (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2018)
AbstractThis study aims to describe the homeworker protection that works on the putting out system. The results of the study indicate that homeworker protection working in a putting out system has not been fully implemented. This can be seen in the bell: there are rules that specifically protect homeworkers working in the putting out system.Keywords: Homeworkers, Putting Out System, Legal ProtectionAbstrakPenelitian ini bertujuan untuk menguraikan perlindungan homeworker yang berkerja secara putting out system. Hasil penelitian menujukan bahwa perlindungan homeworker yang berkerja secara putting out system belum sepenuhnya dilakukan. Hal tersebut dapat dilihat bel;um adanya aturan yang secara khusus melindungi pekerja rumahan yang bekerjas secara putting out system. Kata Kunci: Homeworkers, Putting Out System, Perlindungan Hukum